Comparing conventional aerification practices with the core recycler. Issue 1 (2nd November 2021) - Henry, Gerald; Bowling, William Jackson; Tucker, Kevin
Abstract: Conventional aerification practices on putting greens involve soil core removal followed by sand topdressing, whereas the core recycler reutilizes sand from cores to replenish the soil. Recycling cores may reduce topdressing inputs, sustain plant and microbial activity, and increase fertilizer use efficiency. Research was conducted on a 'Mini Verde' ultradwarf bermudagrass [ Cynodon dactylon (L.) Pers. × Cynodon transvaalensis Burtt‐Davy] putting green established on a sand‐based profile meeting US Golf Association (USGA) specifications at the University of Georgia's golf course during summer in 2017. Treatments were arranged in an incomplete split‐block design; the main block was aerification method (conventional or core recycler) and the subplots were fertilizer treatments. The putting green was halved, with one side aerified to 7.6 cm with a hollow‐tine aerifier. Topdressing sand was applied at a rate of 237 m 3 ha –1 . The second half was aerified to the same specifications (cores not removed), topdressed at 118 m 3 ha –1 (50% of the conventional rate), and passed over with the core recycler. We hypothesized that the aerification method and N fertility would influence organic matter (OM) content, carbon efflux, root biomass, turf color (TC), and normalized difference vegetation index (NDVI). The core recycler produced a greater OM percentage and change in root biomass than conventional aerification, which may be associated with higher TC and NDVI ratings in response to the core recycler treatment. However, OM retention may increase hydrophobic soil conditions and decrease putting green firmness, so rotating the core recycler with alternative techniques is warranted. Core Ideas: The use of the core recycler resulted in greater organic matter retention and root biomass. The use of the core recycler resulted in a short‐term increase in turfgrass color and health. Increases in fertility rates led to an increase in carbon efflux measurements. Neither core aerification nor the core recycler influenced carbon efflux measurements.